Passive Surveillance of Malaria in Pregnant Women, Non-pregnant Women and Children Under 5 Years of Age in Bannu District, Khyber Pakhtunkhwa Pakistan - Qureshi, Humera; Khan, Muhammad Imran; Ahmad, Akhlaq; Awan, Usman Ayub; Khattak, Aamer Ali; Khan, Ayesha Ali; Sun, Yaqiong (Frontiers in Medicine, 2021)
Background: Malaria among pregnant women is one of the major causes of maternal and infant mortality and morbidity, especially in high-risk areas. Therefore, our study identified the burden of malaria for pregnant women, non-pregnant women, and children under 5 years of age, and malaria service health facilities in Bannu district, Khyber Pakhtunkhwa, Pakistan. Methods: A cross-sectional study was conducted. In this survey, 15,650 individuals were surveyed, and 1,283 were malaria-positive detected. The data were collected from 80 different healthcare centers. SPSS version 23 was used for data analysis. ArcGIS version 10.8 was used for study area mapping. Results: Malaria was detected in 23.3% of children under five, 4.4% of pregnant women, and 72.3% of non-pregnant women, respectively. Moreover, P. falciparum, P. vivax, and mixed infection had a prevalence of 2.1, 96.8, and 1.1%. The most often used and effective medications to treat malaria were chloroquine (29.7%) and primaquine (69.4%). Conclusion: This study's findings depict that malaria's prevalence in the non-pregnant women's group was high. Additionally, P. vivax infection was found to be more prevalent than other types of malaria infection. Due to the scarcity of healthcare facilities in this endemic region, special attention should be directed to strengthening the malaria surveillance and eradication programs.